Review on performance and emission of spark ignition engine using exhaust gas recirculation. Issue 2 (1st June 2023) - Pardhi, Chandrakumar; Prasad, Rabindra; Jawahar, C.P.; Chhalotre, Sanjay; Said, Zafar
ABSTRACT: Modernizing electronic control and developing new exhaust gas recirculation (EGR) valves have made it possible to improve EGR accuracy and shorten transient response times. With this paper, we have outlined the findings of research on the effects of various EGR ratios on engine emissions, knock suppression, and charge combustion. Results from experiments conducted by many researchers are summed up as 15% − 18% EGR is found to successfully reduce NOx emissions without impacting engine performance. Because exhaust fumes dilute the fuel/air mixture, this can lead to inefficient combustion, which can lower brake thermal efficiency. According to the findings, selecting the right EGR ratio and spark timing is essential for maximizing engine performance. examined how cold EGR affected knock intensity. It was found that the maximum compression temperature decreased in range of 30–40 kelvin and the cylinder pressure decreased up to 0.4 bar as the EGR increased from 7 to 13%. This demonstrated that the knock was effectively repressed. Because of a buildup of carbon deposits, the EGR valve frequently sticks. In addition to higher fuel consumption or poorer performance, clogged EGRs frequently result in black smoke coming from the exhaust.